Resolving Financing Strategy in Murabahah Transactions at PT. Bank Muamalat Indonesia (BMI) X regional Branch in The Perspective of Islamic Economics - Sada Kolitma; Syaamil Amanulloh (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
This study discusses the Strategy for Resolving Problematic Financing in Murabahah Transactions at PT. Bank Muamalat Indonesia (BMI) X regional Branch from a Sharia Economic Perspective. This study uses a qualitative approach, data collection techniques through interviews, observations, and documents. Data analysis by reducing data, presenting and verifying data. The results of the study indicate that problematic financing in Murabahah transactions at Bank Muamalat Indonesia (BMI) X regional Branch, the main factors of problems in Murabahah transactions are Internal and External Factors. However, after a strategy for handling problematic financing in Murabahah transactions was prepared, the problem could be resolved and has been running effectively. Viewed from a sharia economic perspective, the implementation of Murabahah financing activities at BMI X regional Branch is in accordance with the regulations of the National Sharia Council (DSN) and the Indonesian Ulama Council (MUI). The researcher's suggestion is that BMI X regional Branch should further develop Murabahah financing products, so that they are not only limited to land and building financing only.